Predictors of Antiretroviral Adherence Self-efficacy Among People Living With HIV/AIDS in a Canadian Setting. (1st January 2019) - Lee, William K.; Milloy, Michael John. S.; Nosova, Ekaterina; Walsh, John; Kerr, Thomas
Abstract : Background: Suboptimal adherence to antiretroviral therapy (ART) among people living with HIV/AIDS (PLWHA) who use illicit drugs remains an ongoing health concern. Although health outcomes associated with adherence self-efficacy have been well-documented, there is dearth research exploring the predictors of this construct. This study sought to identify possible determinants of adherence self-efficacy among a cohort of PLWHA who use illicit drugs. Methods: From December 2004 to May 2014, we collected data from the AIDS Care Cohort to evaluate Exposure to Survival Services, a prospective cohort of adult PLWHA who use illicit drugs in Vancouver, Canada. We used multivariate generalized estimating equation analyses to identify longitudinal factors independently associated with higher adherence self-efficacy. Results: Among 742 participants, 493 (66.4%) identified as male and 406 (54.7%) reported white ancestry. In multivariate generalized estimating equation analysis, older age at ART initiation (adjusted odds ratio [AOR] = 1.02, 95% confidence interval [CI]: 1.00 to 1.03) and recent year of baseline interview (AOR = 1.08, 95% CI: 1.05 to 1.11) were independently associated with higher adherence self-efficacy, whereas homelessness (AOR = 0.78, 95% CI: 0.65 to 0.94), ≥daily crack smoking (AOR = 0.81, 95% CI: 0.68 to 0.96), experienced violence (AOR = 0.82, 95% CI: 0.69 to 0.98), and childhood abuse (AOR = 0.75, 95% CI: 0.60 to 0.92) were negatively associated. Conclusions: These findings highlight the potential role that personal and contextual factors can play in predicting levels of ART adherence self-efficacy. Future research should seek to identify and validate strategies to optimize adherence self-efficacy.